Understanding Retirement Transitions: A Comprehensive Review of Theoretical Frameworks - Lertpanyawiwat, Nattha; Dhammasaccakarn, Wanchai; Jeawkok, Jirachaya (Asia Social Issues, 2025)
Retirement is a transformative life event that exerts a substantial impact on the psychological, social, and behavioral well-being of individuals. This article conducts a comprehensive review of diverse theoretical frameworks, encompassing self-determination theory, life-span developmental frameworks, gerontology and aging theories, empowerment theory, social support and social exchange theories, alongside occupational psychology and organizational behavior theories. Utilizing a synthesis approach involving over 30 articles, we meticulously curated a selection of 10 articles closely aligned with retirement theories. This article critically dissects these foundational theories essential for understanding the nuances of retirement. It emphasizes the pivotal role of theoretical frameworks in molding research and shedding light on the multifaceted elements influencing retirement adaptation and overall well-being. These elements span psychological, social, emotional, physical, occupational, financial, relational, and community. In the conclusion, we delve into the implications of employing theoretical frameworks for future research that harmoniously integrates multiple theoretical perspectives. Furthermore, the article posits that these frameworks can serve as the cornerstone for designing effective interventions and programs aimed at aiding individuals in successfully navigating the intricate challenges of retirement transitions.